2012
DOI: 10.1111/j.1365-313x.2012.04947.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of the internal structure of type I protein bodies in rice endosperm: relationship between the localization of prolamin species and the expression of individual genes

Abstract: SUMMARYRice prolamins, a group of seed storage proteins, are synthesized on the rough endoplasmic reticulum (ER) and form type I protein bodies (PB-Is) in endosperm cells. Rice prolamins are encoded by a multigene family. In this study, the spatial accumulation patterns of various prolamin species in rice endosperm cells were investigated to determine the mechanism of formation of the internal structure of PB-Is. Immunofluorescence microscopic analysis of mature endosperm cells showed that the 10 kDa prolamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 45 publications
2
87
0
1
Order By: Relevance
“…Cys-poor prolamins are accumulated at late stages of grain filling [43], and their expression is increased during suppression of glutelins, which are the most abundant storage protein in rice [44]. Both the present data and previous reports suggest that the expression of Cys-poor prolamin is controlled at the mRNA level, and effectively stores excess nitrogen during additional fertilization [43], [44].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Cys-poor prolamins are accumulated at late stages of grain filling [43], and their expression is increased during suppression of glutelins, which are the most abundant storage protein in rice [44]. Both the present data and previous reports suggest that the expression of Cys-poor prolamin is controlled at the mRNA level, and effectively stores excess nitrogen during additional fertilization [43], [44].…”
Section: Resultssupporting
confidence: 75%
“…Cys-poor prolamins are accumulated at late stages of grain filling [43], and their expression is increased during suppression of glutelins, which are the most abundant storage protein in rice [44]. Both the present data and previous reports suggest that the expression of Cys-poor prolamin is controlled at the mRNA level, and effectively stores excess nitrogen during additional fertilization [43], [44]. This may be because Cys-poor prolamin has the simple primary structure with the absence of cysteine residues, and is directly accumulated in the endoplasmic reticulum where protein synthesis occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Protein trafficking and organelle reshaping can also be investigated by looking at the behavior of recombinant proteins, including storage proteins fused to fluorescent tags (Tosi et al, 2009; Saito et al, 2012; Shigemitsu et al, 2013; Wakasa and Takaiwa, 2013) or foreign proteins that have been produced in the context of molecular farming. Endogenous glycoproteins are rarely found in the endosperm (Woo et al, 2001) and are difficult to follow due to the lack of appropriate detection antibodies, so recombinant glycoproteins are particularly useful because they can be traced through intracellular pathways by immunolocalization and by characterizing their glycan modifications (Drakakaki et al, 2006; Arcalis et al, 2010).…”
Section: Recombinant Protein Production In Cereal Endospermmentioning
confidence: 99%
“…In the case of rice proteins, Bradbury et al (16) reported that the decreased protein digestibility due to cooking does not result from the formation of isopeptide linkages between the e-amino group of lysine (which would make it resistant to trypsin degradation) and the g-carboxyl group of glutamic acid residues, but may instead be due to the formation of a cystine-rich core that is resistant to proteases. In addition, Saito et al (17) reported that the localization of prolamin species in PB-Is was different and 16 and 10 kDa prolamin, sulfur-containing amino acids rich in proteins, were mainly located in the core and in the middle layer of PB-Is, respectively. Based on these reports and our results, we hypothesize that hydrophobic interactions and disulfide linkages in the PB-Is contribute to the decrease in prolamin digestibility that occurs with cooking.…”
Section: Excretion Of Rice Proteins In the Fecesmentioning
confidence: 99%